Using Spiritual Connections to Cope With Stress and Anxiety During the COVID-19 Pandemic - Algahtani, Fahad D.; Alsaif, Bandar; Ahmed, Ahmed A.; Almishaal, Ali A.; Obeidat, Sofian T.; Mohamed, Rania Fathy; Kamel, Reham Mohammed; Gul, Iram; Hassan, Sehar un Nisa (Frontiers in Psychology, 2022)
During the initial phases of the COVID-19 pandemic, stress and anxiety were pervasive among the masses due to high morbidity and mortality. Besides the fear of coronavirus was also particularly driven by social media. Many people started to look for faith and spiritual connections to gain comfort. The role of spiritual ties and religious beliefs in relation to coping with pandemic stress has acquired the attention of researchers in some parts of the world. This cross-sectional survey aimed at assessing the intensity of stress and anxiety symptoms experienced by people and how much they were alleviated by employing spiritual connections. The study sample comprises 795 respondents with 52% males and 48% females living in Saudi Arabia. The brief online study questionnaire collected data about background variables, anxiety and stress scale from DASS-21, and items from the WHOQOL (SRBP) instrument assessed the use of spiritual beliefs to cope. Multiple regression models were tested to determine the role of spiritual connections after adjusting demographic variables. Results illustrated that after adjusting for gender and age, participants’ anxiety symptoms decreased by (β = −0.27; p = 0.000) units with each unit increase in the use of spiritual connections, and participants’ stress symptoms reduce by (β = −0.36; p = 0.000) units with each unit increase in coping with spirituality. Additionally, females’ risk to experience anxiety and stress symptoms was more than males [(β = 0.88; p = 0.01) and (β = 0.92; p = 0.000)], respectively. An increase in age decreases the likelihood of experiencing anxiety symptoms and stress symptoms by (β = −0.75; p = 0.02) and (β = −0.11; p = 0.000) units, respectively. Findings support the protective role of spiritual connections despite small beta coefficients. The social and cultural context in Saudi Arabia favors deep-rooted connections with spirituality and faith. Our findings support the fact that the reliance on spiritual connections helped older people to deal with exaggerated fear during the initial phase of the COVID-19 pandemic and reduces the risk of experiencing anxiety and stress symptoms. Females and younger participants were relatively vulnerable to developing these symptoms. We discussed these findings considering some recent studies that reported similar relationships and made recommendations for future research.